Using Arithmetic Weighted and Bhargava Methods to Classify Irrigation Water Quality Index for Shatt-Al Kufa in Najaf Province, Iraq - M. Kizar, Fatima; ., . (International Journal of Engineering and Technology, 2018)
WQI is a mathematical method used to convert the bulk of the information into a single number to express the data in a simplified and explicable form. This study is concerned with evaluating an applicable WQI for irrigation use at several locations on Shatt Al-Kufa. The ten water quality parameters of pH, Electrical Conductivity (EC), Total Dissolved Solid (TDS), Total Hardness (T.H), Calcium (Ca+2), Magnesium (Mg+2), Sodium (Na+), Potassium (K+), Chlorides (Cl-1) and Sulphate (SO4)-2 were studied over a period of twelve months (January to December 2017) for six selected locations, including Zerkh, Kufa, Manathira, Hira, Mashkhab and Qadisiya on Shatt Al-Kufa, Sodium Adsorption Ratio (SAR) was also calculated. Two methods (Weighted Arithmetic and Bhargava) were applied to categorize the WQI of the raw river water for irrigation use, and then a comparison of the two methods was made to determine the difference between them. The Results of the overall, annual and seasonal WQI values according to both Weighted Arithmetic and Bhargava methods were classified as good in all selected locations with the except of some cases in summer, spring and autumn seasons for Weighted Arithmetic which were classified as excellent (0-25). The difference between the two methods is also presented.